(3ehShYI af GdJaUjd hGdNjGWIs - (3NjQj, fLdGAs ((3GdbGgQIs (3ecJHI GHf SjfGs, 2013)
(3jJcde GdcJGH Yf feGPL YedjI JUfjYgG HfaSc eRhOI HGdHJQhfGJ hCSGSjGJ JYde af GdJaUjd h GdNjGWI cJGdhL hCQbj JUejeGJ GdedGHSs
(3GTZGd jOhjIs
11 12
Keywords: (3GdMjGcIs; (3JaUjd GdedGHSs; (3TZd GdGHQIs